Efektivitas Hukum Terhadap Pencemaran Lingkungan Mikroplastik Oleh Produsen Air Mineral di Batam - Fitri, Winda; Nurisman, Eko; Mutiara, Ayu Yulia (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
The use of mineral gallons in Indonesia is something that is often found. Mineral water companies are also competing to innovate their products, both in terms of the composition of the existing mineral water and in terms of the product packaging itself. Then, a new innovation emerged, namely the use of GSP. Even though it is considered efficient enough to use, this innovation actually adds to the threat to the environment. That is why this research aims to find out the effectiveness and ineffectiveness of the enactment of environmental pollution legal regulations which discuss the activity of business actors in minimizing environmental pollution in Batam City. The type of research used in this writing is empirical research or what is usually called empirical legal research. Where secondary data is initial data as a data collection technique and primary data is complementary data obtained directly from the field. Environmental pollution caused by microplastics due to the use of single-use gallons does have a bad impact because plastic is waste that cannot simply be decomposed by natural processes, but this comes back to public awareness and firm decision making by legal stakeholders.